The influence of profitability, liquidity, company size, and corporate social responsibility on earnings management with institutional ownership as a moderating variable - Laili Nadhifa Khoirunnisa; Amalia Ilmiani; Titi Rahayu Prasetiani (Business, Accounting, and Knowledge Journal, 2025)
social responsibility on earnings management with institutional ownership as a moderating variable. Research methods using quantitative methods, data collection techniques using secondary data. The sampling technique uses purposive sampling technique, the sample is 44 companies which are the financial statements of Property and Real Estate companies on the Indonesia Stock Exchange (IDX). The analysis technique used is descriptive statistical test with data processing using WarpPLS 8.0. From the results of the research hypothesis testing shows that liquidity, company size, corporate social responsibility have a positive effect on earnings management, profitability has a negative effect on earnings management, institutional ownership strengthens profitability, liquidity and corporate social responsibility have a positive effect on earnings management, institutional ownership does not moderate company size on management profit.